Penerapan Sistem Rekam Medik Elektronik Dalam Keperawatan Di Unit Rawat Jalan Rumah Sakit Umum Daerah Haji Kota Makassar - Ali Imran; Nurul Muchlisa; Muslimin Burhanuddin; Dian Ekawaty; Adriyani Adam (Media Kesehatan Politeknik Kesehatan Makassar, 2023)
The Medical Record Information System (SIRM) will simplify the patient health examination process with integrated access to medical record data, thereby reducing the error rate in the examination process. Research objectives: To find out how the electronic medical record system is implemented in nursing in the outpatient unit of RSUD Haji Makassar. This research is a type of quantitative research that uses a cross-sectional study design approach. The sample for this study consisted of 80 nurses who worked in the outpatient unit of RSUD Haji Makassar. the implementation of an electronic medical record system is seen from work expectations, business expectations, social influence and facility conditions. Work expectations will simplify the process of documenting nursing care, business expectations will make it easier or reduce individual efforts to do work, social influences are more about how they influence behavioral decisions and facility conditions will maintain patient efficiency, safety and quality Keywords: work expectations, business expectations, social influence, facility conditions